CONFLITOS SOCIAIS E DIREITOS HUMANOS: ALTERNATIVAS ADEQUADAS DE TRATAMENTO E RESOLUÇÃO - Bohn, Ana P. d. S.; Formentini, Francieli; Maschi, Angela; Pinheiro, Jane M. d. A. (Salão do Conhecimento, 2013)
Resumo